DIVERSITY OF ORNAMENTAL PLANTS IN DESA COT GUT REGENCY'S HOUSE YARD, NAGAN RAYA DISTRICT - Ulia Hanum; Mauizah Hasanah (Jurnal Biologi Sains dan Kependidikan, 2023)
Humans can form a community with a certain diversity of plant species according to the desired environment, such as ornamental plants and protective plants in yard.  The yard of residents’ houses in Cot Gut Village, Nagan Raya Regency, have many diverse plant species, especially from the ornamental plant group. However, these ornamental plants have not been taxonomically recorded and inventoried. This study aims to determine the species richness and the level of diversity of ornamental plant species found in the yards of residents in Cot Gut, Nagan Raya. Data collection used a field survey method, to see the richness of ornamental plant species found in the research location. Data from the field were analyzed using the Shannon – Wiener Diversity Index. The results obtained were 20 Species of ornamental plants from 18 families with a total number of 269 individual ornamental plants from 20 yards of residents’ houses in Cot Gut Village, East Seunagan District, Nagan Raya. The Species Diversity Index (H') value of ornamental plants in the yards of residents' houses in Cot Gut Village, Nagan Raya are 2.723.